‘Mizh der beitabora khalqi-i’: A comparative study of Afghan/Pashtun perspectives on negotiating with the British and Soviets, 1839–1989 - Johnson, R (Routledge, 2011)
This article compares the processes of negotiation in Afghanistan in two distinct eras in order to highlight the enduring characteristics of concluding wars and the unique specificities of history. The problem of obtaining reliable sources on the Afghan reactions to negotiations is to some extent offset by an awareness of theoretical approaches and common features of negotiations within the contexts of other conventional and civil wars. The two case studies presented in outline here suggest that there were peculiarities to Afghans based on cultural expectations, but, like their British and Soviet opponents, they took a pragmatic approach to fulfil their own interests. The article concludes with some observations on the potential for future negotiations.